Dramaturgy and the Phenomenon of Instagram Multi-Account Usage Among Gen Z in Bali - Winduwati, Septia; Irena, Lydia (Jurnal Komunikasi, 2024)
Generation Z, born between 1997 and 2012, has grown up in a digital technology era that has shaped their communication and interaction styles, particularly through social media platforms like Instagram. They are highly active on this platform, with 58% spending more than an hour each day. This study aims to analyze how Generation Z utilizes multiple accounts on Instagram using Erving Goffman's dramaturgical theory, which describes social interactions as performances where individuals play roles according to social contexts. This research is expected to contribute to understanding the construction of digital identities and social roles of Generation Z. A qualitative approach is used in this study to describe the findings from Generation Z Instagram users with multiple accounts in Bali. Data were collected through in-depth interviews, field observations, and document studies, and analyzed using thematic analysis techniques. The results indicate that Generation Z uses multiple Instagram accounts to separate "front stage" and "back stage" in their identity management. The main account serves for personal branding and professional image, while the secondary account is used for more free-form self-expression. However, although multi-account management helps in managing identities, some informants still experience conflicts in maintaining their image on the main account and authenticity on the secondary account. Identity management in this digital era reflects their ability to navigate diverse social demands and balance public image with personal expression in the digital world.